Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3892/mmr.2022.12744
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic alternations of RANKL/OPG ratio expressed by cementocytes in response to orthodontic‑induced external apical root resorption in a rat model

Abstract: The aim of the present study was to investigate the alterations in the formation of cementocytes in response to orthodontic forces and to evaluate the contribution of these cells in the biological changes of tooth movement and associated root resorption. A total of 90 Sprague Dawley rats were randomly assigned to the control, high force, and low force groups. Intrusion forces of 10 and 50 g were applied on the rat molar to induce tooth intrusion. The tooth movement was observed from 0 to 14 days by micro-compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Regarding bone formation mediators, the most studied one (investigated by 87 % of the animal studies) is osteoprotegerin (OPG). Several studies reported a decrease in OPG expression and/or levels at distinct time points in animal models after both 10- and 50-g intrusion [ 40 ] and 80- to 100-g to produce inclination [ 27 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding bone formation mediators, the most studied one (investigated by 87 % of the animal studies) is osteoprotegerin (OPG). Several studies reported a decrease in OPG expression and/or levels at distinct time points in animal models after both 10- and 50-g intrusion [ 40 ] and 80- to 100-g to produce inclination [ 27 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Besides the abovementioned alterations, the main alternative biological response occurring along the mechanical loading was an increase of coarse and irregular fibers and blood capillary compression in rodents [ 16 , 25 , 28 , 29 ]. Also, it should be noted that three studies observed that heavier forces were not associated with a greater amount of tooth movement when two or more levels of forces (3–100 g) were assessed [ 29 , 33 , 37 , 40 ], when producing different types of movements. On the other hand, one study detected a significantly higher OTM under 100-g force compared to 30 g [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RANKL is produced by osteoblasts and osteocytes, and binds to its receptor RANK on the surface of osteoclasts [ 107 ]. This interaction activates a signaling cascade that leads to the differentiation, activation, and survival of osteoclasts, resulting in bone resorption [ 108 ]. During orthodontic tooth movement, RANKL expression increases in gingival crevicular fluid in juvenile patients [ 109 ].…”
Section: Orthodontic Tooth Movement and Osteocyte Signaling Pathwaysmentioning
confidence: 99%